GEOGRAPHIES THAT MADE HISTORY - Francesco Micelli (Bollettino della Società Geografica Italiana, 2019)
A first day, organized by Claudio Cerreti and Claudio Minca, on the theme Geographies that Made History – The 80s, was held at the University «Roma Tre», February 27, 2014. The discussion focused on three books: Social Formation and Symbolic Landscape (1984) by Denis Cosgrove; The Metaphors of the Earth (1985) by Giuseppe Dematteis; For a Geography of Power (1981) by Claude Raffestin. On the second day, by the same organizers, the interest turned to three handbooks: An Introduction to Human Geography (1986) by Pasquale Coppola, Human Geography by Costantino Caldo (1979), Region and Territory by Adalberto Vallega (1976); the conference proceedings of Region and Regionalization, edited by Angelo Turco, held in Verona (1984). During these meetings, always coordinated by Franco Farinelli, a young geographer and a geographer of a different generation have reasoned jointly on texts to capture the moment of the rebirth of geographical thought in Italy. Lida Viganoni and David Papotti have conversed on An Introduction to Human Geography. Girolamo Cusimano and Marco Picone on Human Geography, Egidio Dansero and Paola Morelli on Region and Territory. While handbooks synthesize an important body of research carried out, Cerreti examine the thesis of the Verona symposium, dominated by Vallega’s proposals according to which general system theory would solve the epistemical needs of geography. Farinelli emphasize the potential knowledge base not yet exploited of geography. He stresses the critiques towards theories adopted from different disciplines without a specific research activity. He finally concludes underlining the relevance of the geographer profile free from constrains which are not science itself.